Endoscopic transcecal appendectomy: a new endotherapy for appendiceal orifice lesions - Guo, Linjie; Ye, Liansong; Feng, Yilong; Bethge, Johannes; Yang, Juliana; Schreiber, Stefan; Hu, Bing (Endoscopy, 2021)
Background Endoscopic transcecal appendectomy (ETA) has been reported as a minimally invasive alternative procedure for lesions involving the appendiceal orifice. The aim of this case series study was to evaluate the feasibility, safety, and effectiveness of ETA for lesions at the appendiceal orifice.Methods This retrospective study included consecutive patients with appendiceal orifice lesions who underwent ETA between December 2018 and March 2021. The primary outcome was technical success. The secondary outcomes included postoperative adverse events, postoperative hospital stay, and recurrence.Results 13 patients with appendiceal orifice lesions underwent ETA during the study period. The median lesion size was 20 mm (range 8–50). Lesions morphologies were polypoid lesions (n = 5), laterally spreading tumors (n = 4), and submucosal lesions (n = 4). Technical success with complete resection was achieved in all 13 cases. There were no postoperative bleeding, perforation, or intra-abdominal abscess. The median length of hospital stay after ETA was 8 days (range 6–18). There was no tumor recurrence during a median follow-up of 17 months (range 1–28).Conclusions ETA is feasible, safe, and effective for complete resection of appendiceal orifice lesions. Larger, multicenter, prospective studies are needed to further assess this technique.